Procompetitive infrastructure sector regulation and diffusion of innovation: The case of broadband networks - Harald Gruber; Pantelis Koutroumpis (International Telecommunications Society (ITS), 2011)
The paper assesses the scope for competition inducing infrastructure regulation in furthering the diffusion of innovation. The paper uses data on the adoption of broadband services comprising a global panel of 167 countries. The effects of different regulatory provisions are assessed. The result of this paper allows qualifying different elements of the regulatory debate on the consequences of access requirements, including mandatory unbundling. First, it suggests that interplatform competition is generally not leading to acceleration in broadband diffusion. Second, with respect to intra-platform competition, this has been analyzed at two different levels: full unbundling and retail competition. In the first case the competitor is investing in network infrastructure to be able to induce some degree of service differentiation. With retail competition the scope for service differentiation is much more limited and hence competition is most likely centered on price. While both lead to faster diffusion, the results consistently show that the effect from retail competition is proportionally about twice as strong compared to unbundling. Moreover, the analysis of the time profile of the effects show that this impact on diffusion first increases until the third or fourth year after introduction, but then dissipates away. Also here one can argue that retail differentiation leads to more intense price competition and therefore faster diffusion. Different robustness checks for the results are provided.
Keywords: L96; L51; O33; 330; Broadband; regulation; innovation; service competition; platform competition; local loop unbundling